The breakdown of the system of strategic stability and possible scenarios for the future - Pérez Gil, Luis V. (Journal of the Spanish Institute for Strategic Studies, 2020)
In this paper, we argue that the international system has undergone acomplete transformation in a few short years and that the possibility of itscomplete destruction has increased several hundredfold during this time.Consequently, it seems fitting to reflect upon an issue that has been raisedon more than one occasion: Is a third world war imminent? Has decision-making reached the point of no return? The phrase, ‘no, it cannot be,’has changed to ‘yes, it can, if we believe we have something to gain’. Theseare the devastating consequences of ignorance, disdain for diplomacy, a falsesuperiority complex and, most especially, the suicidal tendency that humanity as a whole has been cultivating since the beginning of time. The hugeadvances in technology can be envisaged alongside extinction because, inreality, some will survive on a dead planet. This may be the end of civilisation as we know it and the dawn of a new civilisation in a different world.These are hard questions to ask. But we ask them nevertheless. Even thoughwe have no clear answers.
Keywords: Global security; strategic stability; arms-control; INF Treaty; nuclear weapons